Activating the Heart: Storytelling, Knowledge Sharing and Relationship (Christensen, Julia, Christopher Cox and Lisa Szabo-Jones, eds.) - Garroutte, Eva Marie (Transmotion, 2019)
Review by Eva Garroutte